Elucidating the Effects of Winning and Losing Positions on the Relationship Between Football Supporters’ Satisfaction and Behavioral Intentions According to Weiner Attribution Theory - Jamil Nawkhasi; Saeed Sadeghi Boroujerdi; Ali Mohammad Safania; Sayed Salah Naghshbandi (Research in Sport Management and Marketing)
Purpose: The goal of this study was to elucidate effects of winning and losing positions on the relationship between football supporters’ satisfaction and behavioral intentions according to Weiner Attribution Theory.Methods: The research is in consonance with applied objective and methodologically correlation- descriptive. The statistical population of this study was conducted on Perspolis and Esteghlal Tehran team supporters in season 98-99. Sample size was appraised qua 277 individuals for each team (554 in general) based on SPSS sample power software. Sampling method was employed accessibly after the end game, while spectators wear leaving the stadium. (Azadi Tehran stadium). For the test model, structural equation modeling approach to multi-group analysis was used.Results: The study findings showed that the only significant factors are game satisfaction path coefficient and purchase intention (t=2.537, β=-0.280), while in winning position, service satisfaction path coefficient on purchase intention (t=2.313, β=0.190), game satisfaction on purchase intention (t=6.599, β=0.550) and game satisfaction on attendance intention (t=5.039, β=0.477) was recognized significantly.Conclusions: adapted from this result, supporters’ behavioral response is affected by game positions. Whereas game position is inevitable, (losing and winning is incontrollable as sports modality) it is suggested to the club authorities to strengthen supporters’ emotional states through submission services.